Research Value of Intensity Modulated Radiation Therapy in Alleviating Parotid Gland Function Injury in Patients with Stage N0 Nasopharyngeal Carcinoma from Physical and Dosimetric Aspects. (11th July 2022) - Zheng, Lirong; Wang, Hong; Yang, Neng; Du, Fenglei; Xiao, Lin; Wu, Gangfeng
Abstract : Objective . To study the feasibility of intensity modulated radiation therapy (IMRT) for stage N0 nasopharyngeal carcinoma (NPC) and its parotid gland (PG) function preservation from physical and dosimetric aspects. Methods . All the clinical data of 77 patients with pathologically confirmed T1-4 N0 M0 NPC who received radiotherapy between July 2017 and October 2019 in the Radiotherapy Center of Taizhou Hospital of Zhejiang Province affiliated to Wenzhou Medical University were analyzed retrospectively. Three-dimensional conformal radiotherapy (3D-CRT) and IMRT were used in 35 and 42 cases, respectively. The treatment efficiency and the dosimetry differences of the PG in the intensity modulation plan were compared between groups. Quantitative monitoring of 99mTc radionuclide imaging of PG was performed before, at the end of, and 3, 6, and 12 months after radiotherapy. The degree of PG function injury and xerostomia was compared between groups at the end of radiotherapy and 12 months later. Results . Higher minimal, maximal, and average irradiation doses of PG were determined in 3D-CRT-treated patients compared with IMRT-treated cases (P < 0.05 ). Compared with before radiotherapy, the PG uptake index (UI) and excretion index (EI) of both cohorts of patients decreased to varying degrees at the end of radiotherapy, with PG function injury and xerostomia symptoms observed in all cases but with no obvious difference between groups (P > 0.05 ). To a certain extent, the PG function recovered and the xerostomia symptoms relieved in both groups 12 months after radiotherapy, with better improvements in IMRT group versus 3D-CRT group. Conclusion . IMRT has similar short-term efficacy to 3D-CRT in treating patients with stage N0 NPC, but it can effectively reduce the dose of PG radiotherapy and protect the PG function on the premise of ensuring sufficient tumor coverage and dose, showing certain dosimetry advantages.